Population Interference of Glyphosate Resistant and Susceptible Ryegrass on Eucalyptus Initial Development - BRAGA,A.F. (2018)
ABSTRACT: The repetitive use of herbicides with the same mechanism of action causes the selection of resistant weeds, such as ryegrass. Considering the occurrence of ryegrass (Lolium multiflorum) in eucalyptus, a crop on which glyphosate is used, it is necessary to study its interference. The objective of this study was to evaluate the effect of densities (0, 10, 20, 30 and 50 plants m-2) of two ryegrass biotypes (resistant and susceptible to glyphosate) on seedlings of two eucalyptus clones (I-144 and 1407). The used experimental design was in randomized blocks with four replications, following a 2 x 5 factorial arrangement for each clone. The height and diameter of the clones were evaluated at 0, 14, 28, 42, 56 and 70 days after transplantation (DAT), and at 70 DAT, the leaf area and dry biomass of eucalyptus and ryegrass were also evaluated. There was no interaction between the biotype and densities factors for the clones, but all characteristics were affected by the factors separately. The increase in ryegrass densities affected all the characteristics evaluated in the clones, being the leaf area of the eucalyptus clones the most affected one, with reductions of up to 72%. The resistant biotype was less competitive, causing reductions in clones of up to 39% in leaf area, 5% in diameter and 1% in height, while the susceptible biotype resulted in reductions of 51%, 13% and 6%, respectively. Thus, the tolerable density by the culture to the resistant biotypes may be greater than that of the susceptible biotypes.